Integration of Anti-SLAPP in the Reform of the Indonesian Criminal Procedure Code in an Effort to Protect Human Rights - Muhni, Afif; Basri, Muhammad; Rivanie, Syarif Saddam; Iskandar, Ismail; Muin, Audyna Mayasari; Mirzana, Hijrah Adhyanti (SIGn Jurnal Hukum, 2025)
Public participation in Indonesia faces a threat of systematic criminalization due to a procedural legal vacuum in Law Number 8 of 1981. This loophole enables the abuse of the legal process through SLAPP, a practice that silences critical voices and delegitimizes the constitutional guarantees for Human Rights. This study aims to analyze the urgency of and formulate a normative framework for comprehensively integrating an Anti-SLAPP mechanism into the Criminal Procedure Code Bill. Using a normative legal research approach, this study examines the disharmony between substantive protection norms and the absence of procedural enforcement instruments. The analysis reveals that without an early screening mechanism, a rule for shifting the burden of proof, and the recognition of a public interest defense, Law Number 8 of 1981 structurally fails to protect citizens. Therefore, this study recommends the integration of an inclusive and non-sectoral Anti-SLAPP mechanism into the Criminal Procedure Code Bill, designed to protect not only conventional activism but also participation in the digital space. This step is a fundamental prerequisite for strengthening the rule of law, fulfilling commitments to SDG 16, and ensuring the resilience of Indonesian democracy in the future.